Can Charitable Donations Compensate for a Reduction in Government Funding? The Role of Information. (12th February 2020) - de Wit, Arjen; Bekkers, René
Abstract: Are private donors willing to replace cuts in government funding? The authors conducted a survey experiment (n = 2, 458) to examine how information about government funding affected decisions to donate money to a large charitable organization in the Netherlands. Providing information about actual budget cuts increased the number of donors. Most new donors were recruited among respondents who had processed the information correctly, underlining the importance of effective communication. The magnitude of the information effect was stronger for citizens with lower levels of empathic concern, who are less likely to donate but can be converted into donors. The authors conclude that policy information shapes not only attitudes but also civic engagement outside the political sphere .